Kajian Tingkat Kadar Pirit (FeS2) Tanah Pada Lahan Rawa Pasang Surut di Desa Barambai Kolam Kiri, Kabupaten Barito Kuala, Kalimantan Selatan - Novianti, Vina (Universitas Sebelas Maret, 2019)
South Kalimantan is a potential region of Indonesia to develop local rice plants with adaptation to tidal swamp. This study aimed to identify the level of soil pyrite on tidal swamp land in BarambaiKolamKiri Village, Barito Kuala Regency, South Kalimantan. The method used in this research was a survey method in which observation and soil sample were taken systematically based on soil depth. Soil sampling for the direct qualitative test was carried out using a soil auger. Soil profile for observation of soil morphological characteristics was determined based on the result of the soil auger data. The data of soil resulted from field and laboratory analysis were used to compare soil characteristics and level of soil pyrite among horizon. The morphological soil characteristics observation in tidal swamp land showed that the profile thickness was 0-120 cm, there are two types of horizon including horizon A and B, soil color was grayish brown to dark gray, texture was sandy loam and clay loam, and soil consistency were sticky and plastic. Based on the six soil layers tested, three different pyrite levels were identified: low, medium and high. The results of this study will be used to develop local rice plants with adaptation to high pyrite in tidal swamp land.